2020 25th International Conference on Pattern Recognition (ICPR) 2021
DOI: 10.1109/icpr48806.2021.9413308
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised deep learning for text line segmentation

Abstract: We present an unsupervised text line segmentation method that is inspired by the relative variance between text lines and spaces among text lines. Handwritten text line segmentation is important for the efficiency of further processing. A common method is to train a deep learning network for embedding the document image into an image of blob lines which are tracing the text lines. Previous methods learned such embedding in a supervised manner, requiring the annotation of many document images. This paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We compare our results with those of supervised learning methods, Mask-RCNN [14] and FCN+EM [14], and an unsupervised deep learning method, UTLS [15]. Mask-RCNN is an instance segmentation algorithm which is fully supervised using the pixel labels of the text lines.…”
Section: Results On the Vml-ahte Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…We compare our results with those of supervised learning methods, Mask-RCNN [14] and FCN+EM [14], and an unsupervised deep learning method, UTLS [15]. Mask-RCNN is an instance segmentation algorithm which is fully supervised using the pixel labels of the text lines.…”
Section: Results On the Vml-ahte Datasetmentioning
confidence: 99%
“…The advantage of the proposed method on the supervised methods is zero labelling effort. Also UTLS [15] has zero labelling effort, however it requires to adjust a heuristic formula. The proposed method eliminates this formula by assuming the neighbouring patches contain the same text line patterns.…”
Section: Results On the Vml-ahte Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Barakat et al [9] suggested an unsupervised method for extracting text lines, which was driven by the relative variation in text lines and space between text lines. The number of foreground pixels over text lines differs significantly from the number of foreground pixels over text line gaps.…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge, there is no existing work that assigns a corresponding order to text translations. Of course, there are some works dealing with document layout, such as text line extraction [1,2], text line segmentation [3,4], and scene text detection [5]. Tere are also several works on recognizing characters such as Gurmukhi [6][7][8][9][10][11] and Devanagari [12], as well as a work on machine translation [13].…”
Section: Introductionmentioning
confidence: 99%